Risk Assessment and Recommendation Strategy Based on COBIT 5 For Risk - A Case Study of an Internet Service Provider Company - Setiawan, Jeremy; Fianty, Melissa Indah (Journal of Information Systems and Informatics, 2023)
Information technology governance is part of organizational management that includes leadership and ensuring that information technology has a broad scope to meet needs. The concept of IT Governance is a method of managing technology users in. The company, in this case, provides IT needs and solutions to customers ranging from hardware, software, and services. A good business case will include the problem in information technology governance, especially when it comes to maintenance related to POP or Post Office Protocol which is the internet protocol used on TCP/IP networks such as the internet. In this study, the framework used as a reference in IT development is COBIT 5. The domain processes studied are EDM02 – Ensure Benefits Delivery, APO07 – Manage Human Resources, and APO10 – Manage Suppliers, who can evaluate IT governance at this Company. The research method used is Gallego’s Theory starting from planning, field inspection, reporting, and follow-up. The results of this study were obtained from the evaluation of information technology governance in the Company got to level 1 capability with fully achieved achievement but could not move up to the next stage, that is, level 2, resulting in a gap analysis of 1 level from the target level expected by the Company.